Effect of Modification Rules in Competition on Technical–Tactical Action in Young Tennis Players (Under-10) - Gimenez-Egido, José María; Ortega-Toro, Enrique; Palao, José M.; Verdú-Conesa, Isidro; Torres-Luque, Gema (Frontiers in Psychology, 2020)
Adapting competitions to young players’ characteristics is an important pillar in the optimal teaching-learning process. The objective of the present study is to analyze the effect of modifying net height (from 0.91 m to 0.80 m) and court dimensions (from 23.77 x 8.23 m to 18 x 8.23 m) for under-10 (U-10) tennis players on the following: a) kinds of technical and tactical basic, situational, and special strokes; b) tennis players’ hitting area; c) landing location of serve; d) ball landing location after the serve; d) stroke effectiveness; and e) rally length. The study design was quasi-experimental in nature, observing the fluctuation/change in technical-tactical variables of the tennis players when playing a “Tennis 10s Green Competition” (GC) with the current federative rules, and a redesigned competition “Modified Competition” (MC) including altered net height and court dimensions based on small-sided games (SSGs) and equipment scaling. Twenty U-10 tennis players were studied (age of players = 9.46±0.66 years, average weekly training in tennis = 2.90±1.07 hours, years of experience = 3.65±1.53 years). The results showed that in MC, there was a greater technical-tactical variability compared to the GC in terms of the following: a) greater service effectiveness; b) more situational and special strokes; and c) a more equitable change in the distribution of hitting and ball landing locations. The values of MC showed that the current adaptation rules and equipment in federated U-10 competitions might not be enough to improve the teaching-learning process under the comprehensive approach. The current competition for U-10 tennis players (stage green) should be redesigned, in order to build an optimal process of affordances to develop a multidimensional positive impact during this training stage.